Back To Basics - The Series R-C Circuit

Download as pdf or txt
Download as pdf or txt
You are on page 1of 3

Back to Basics: The R-C Circuit

Introduction: Electrical engineers must surely know how to analyze the circuit in Figure 1. It
should be second nature to all of us. But I wonder how many of us remember how to derive the
solution. How would you teach it to a student who’s
starting from scratch with just the V-I characteristics of
v=i R for a resistor and i=C dv/dt for a capacitor? As a
tutor of Circuit Analysis student, I came to thinking
about this just recently and I came up with a lesson that
teaches this basic subject without any assumptions or
missing steps.
It starts with deriving the circuit equation. KVL and
Figure 1 The Series R-C Circuit
Ohm’s law gives us…
vs = iR + vc
dvc
and since, i = C ,
dt
dvc
RC + vc = vs [1]
dt

A complete solution combines the particular solution for the given source with the solution for
vs=0. That source-free solution is usually the first part taught to the new student.

How do we know that the source-free solution is an exponential?: In the


absence of an applied source, there can still be a response if there’s an initial charge on the
capacitor producing vc(0) = Vo. At this point, the experienced EE knows the answer. For…
dvc
RC + vc = 0 [2]
dt

a solution that is infinitely differentiable is given by…


t
vc (t) = V0 e− ⁄RC [3]
I’ve taught this solution by explaining the property by which exponentials are proportional to
their own derivatives but that’s like saying, “It’s the solution because it’s the solution.” In fact,
we can prove that [2] is the solution and here’s how.
Equation [2] gives us a formula for the first derivative of vc(t)…
dvc (𝑡) 1
= (− RC) vc (t) [4]
dt

We can differentiate both sides [4] to find the second derivative…


d2 vc (𝑡) d dvc (𝑡) d 1 1 2
= dt ( ) = dt ((− RC) vc (t)) = (− RC) vc (t) [5]
dt2 dt
By the same reasoning,
d𝑘 vc (𝑡) 1 𝑘
= (− RC) vc (t) [6]
dt𝑘

For such a function that is infinitely differentiable, the Maclaurin series expansion (Taylor series
about t=0) is
dvc (t) d𝑛 vc (𝑡) 𝑡𝑛
vc (t)=vc (0)+ ( | ) t + ∑∞
n=2 [( | ) 𝑛! ] [7]
dt t=0 dt𝑛 𝑡=0

Using Equations [3-6]…


𝑡 V 𝑡 𝑛
vc (t)=V0 + V0 (− RC) + ∑∞ 0
n=2 [ 𝑛! (− RC) ] [8]

Equation [8] is the solution to Equation [2] for vc(0) = V0 expressed as a power series.
We can express it in closed form by the following derivation. First, we define a new function,
vc (t) x
f(x, t) ≜ ( ) [9]
V0

Then to expand f(x,t) into a Maclaurin series in t we find…


vc (t) x vc (0) x
f(x, 0) = ( ) =( ) =1 [10]
V0 V0

and
x−1 vc (t) x−1 x
∂f(x, t) vc (t) 𝑑 ⁄V vc (t) 1 vc (t) 1 vc (t) 𝑥
0
= 𝑥( ) = 𝑥( ) [(− ) ] = (− ) ( ) = (− ) f(x, t)
∂t V0 𝑑𝑡 V0 RC V0 RC V0 RC

So that
∂f(x,t) 𝑥 𝑥
| = (− RC) f(x, t) = (− RC) [11]
∂t 𝑡=0

Also
∂2 f(x, t) ∂ ∂f(x, t) ∂ 𝑥 𝑥 2
= ( ) = ((− ) f(x, t)) = (− ) f(x, t)
∂t 𝑥 ∂t ∂t ∂t RC RC

and, in general,
∂𝑛f(x,t) 𝑥 𝑛
= (− ) f(x, t) [12]
∂t𝑛 RC

so that
∂𝑛f(x,t) 𝑥 𝑛
| = (− ) [13]
∂t𝑛 𝑡=0 RC

Using these results, the Maclaurin series expansion of f(x, t) is


vc (t) x xt xt
n
1
f(x,t)= ( ) =1+ (− RC) + ∑∞
n=2 [(− RC) ] [14]
V0 n!

vc (xt)
Comparing [14] to [7] we find that the right side of Equation [14] is .
V0

This means that…


vc (xt) vc (t) x
=( ) [15]
V0 V0

If we set t=-RC and x=-τ/RC,


vc (−RC) −τ/RC 1 −τ/RC
vc (τ)=V0 ( ) = V0 [2+ ∑∞
n=2 (𝑛!)] [16]
V0

The term inside the brackets is a constant that can be evaluated to arbitrary precision by
summing through a sufficient number of terms. Through fourteen decimal points, the value is…

1
[2+ ∑ ( )] = 2.718 281 828 459 05
𝑛!
n=2

This is precisely the value of Euler’s constant, e!


dvc
And that is precisely why the solution to RC + vc = 0 for vc(0) = Vo is { Drum roll, please}
dt

𝐭
𝐯𝐜 (𝐭) = 𝐕𝟎 𝐞− ⁄𝐑𝐂

You might also like